Resolução de Problemas: um olhar sobre as dificuldades apresentadas por alunos de 5º ano e proposta de sequência didática - Del Rovere, Monise Bacci (Universidade Federal de São Carlos, 2022)
The present work aims to identify the difficulties that students find in problem-solving activities, in order to identify and solve these obstacles in order to facilitate the learning of math. The research was developed taking into account both theoretical and practical aspects. The research methodology used was based on the principles of Didactic Engineering. As a theoretical framework for the present work, renowned authors were used who addressed the importance of problem solving for the development of students’ logical mathematical reasoning and as a tool that helps the teaching and learning process. The importance of working on reading and writing in mathematics classes and the concept of literacy was also addressed. Finally, it was commented on the mathematical operations, important aspects in their learning, as well as possible difficulties that students may present. After, bibliographic studies and definition of the target audience of the research, a questionnaire was prepared for the parents of the students about their observations regarding the difficulties of their children with regard to problem solving. A list of activities was later elaborated for the students of the 5th year of elementary school to carry out, seeking to observe the difficulties encountered by the children. After that, interventions were made by the teacher in relation to the main points observed and new activities were applied to observe the Evolution of the students. It was evident that, after the teacher's intervention, the students showed progress, either in mathematical operations or in the interpretation of problems, thus demonstrating the importance of the teacher's attentive look towards the student, looking for strategies to assist their teaching and learning process.
Problem Solving: a look at the difficulties presented by 5th grade students and a proposal for a didactic sequence
Keywords: Resolução de problemas; Leitura e escrita; Operações; Engenharia didática; CIENCIAS EXATAS E DA TERRA::MATEMATICA